Efficient wireless sensor network using nodes sleep/active strategy - Rajesh, L.; Reddy, C.R. Byra (2016 International Conference on Inventive Computation Technologies (ICICT), 2016)
WSN considering clustering mechanism for optimization of energy is very popular among the researchers here also author used clustering mechanism in densely deployed sensor network. Intra cluster and inter-cluster communication is considered, for large distance communication relay nodes are used to reduce the energy consumption. A tradeoff between node density and sleep/active nodes are establish, sleep nodes concept in WSN is useful in reduced the overall energy consumption. Result obtained in terms of node decay rate, network life time, and percentage of active nodes shows that our proposed model for Wireless sensor network based on nodes sleep/active concept is better when compared with existing system.